Synthesis of 1-(2-Hydroxyphenyl) Dec-2-en-1-One Oxime and Its Flotation and Adsorption Behavior for Malachite - Li, Liqing; Yang, Lin; Li, Fangxu (Frontiers in Chemistry, 2020)
A novel collector of 1-(2-hydroxyphenyl) dec-2-en-1-one oxime (HPDO) firstly synthesized from 2-hydroxy acetophenone and octanal, and its flotation and adsorption behavior for malachite were studied by flotation tests and x-ray photoelectron spectroscopy (XPS) analysis. The flotation results of a single mineral show HPDO is a special collector for malachite. Compared with benzohydroxamic acid (BHA), isobutyl xanthate (SIBX) and dodecylamine (DA), HPDO exhibits excellent flotation performance to malachite and satisfied selectivity against quartz and calcite over a wide pH range. The HPDO with concentration of 200 mg/L can float 94% malachite at pH 8, while only recover 7.8% quartz and 28% calcite. XPS data give clear evidences for the formation of Cu-oxime complex on malachite surfaces after HPDO adsorption.